Implementasi Metode Accrual Basis Pada Sistem Informasi Keuangan - Khofifah Haq; Suendri Suendri (Journal of Information System Research (JOSH), 2023)
The financial recording system is carried out in the school diary, so it takes time to recap the revenue or expenditure records in order to find out the amount of funds that have been received or spent. This is less time efficient in presenting financial statements. This study aims to apply the accrual basis method to the financial accounting information system of MIS Nurul Huda Sei Paham and build a web-based financial accounting information system at MIS Nurul Huda Sei Paham. This research uses the research and development method or commonly known as R&D which has several stages, namely potential and problems, data collection, product design, design validation, design revision, product trials, product revision, trial use, final product revision, and mass production. However, this research only reached the product trial stage. System testing uses a questionnaire which is divided into 3 parts, namely expert experts, field tests and prospective users. From the results of the expert questionnaire assessment, a value of 3.8 was generated which indicated a fairly valid category, the field test questionnaire assessment resulted in a value of 4.0 which indicated a valid category and an assessment of a questionnaire of 10 prospective users resulted in a value of 80 which indicated an effective category. it can be concluded that the financial accounting information system using the accrual basis method at MIS Nurul Huda Sei Paham has run well according to school needs and can help present financial reports quickly.